Expression and Histopathological Significance of Disabled-2 in Aldosterone-Producing Adenoma - Li, Ping; Zhang, Min; Ma, Jian-Qiang; Sun, Qi; Liu, Guang-Xiang; Zhao, Xiao-Zhi; Feng, Wen-Huan; Shen, Shan-Mei; Guo, Hong-Qian; Zhu, Da-Long (Hormone and Metabolic Research, 2017)
The current pathological diagnosis of aldosterone-producing adenoma (APA) is challenging because no histological markers of aldosterone production are available in routine practice. A previous study demonstrated that Disabled-2 (DAB2) is a specific marker of the zona glomerulosa (ZG) in rodents. The aim of the present study was to investigate the significance of immunohistochemical staining to detect DAB2 in the adrenal tissue of patients with APA. We investigated the expression of DAB2 in 36 adrenal glands with APA, 23 adrenal glands with cortisol-producing adenoma (CPA), and 33 adrenal glands with non-functioning adenoma (NFA). Immunohistochemical staining was performed using anti-DAB2 antibodies on paraffin-embedded sections. We analysed the expression of DAB2 semi-quantitatively by scoring staining intensity, and assessed the correlation of this information with the clinical findings. DAB2 mRNA expression in adenoma tissues was evaluated by RT-PCR. DAB2 was highly expressed in the ZG in normal human adrenal glands. DAB2 expression was heterogeneous in APA, with spotted, strong staining noted in most samples (25 of 36 APA). CPA and NFA also exhibited extensive low or moderate DAB2 expression. DAB2 mRNA was significantly increased and positively correlated with CYP11B2 in APA (p<0.05). In APA, the DAB2 score adjusted for tumour volume was positively correlated with plasma aldosterone (p<0.05). Patients with low or moderate DAB2 staining more frequently exhibited high blood pressure and were diagnosed at a younger age compared with patients with high DAB2 staining. The present study clearly demonstrates that DAB2 is a specific marker of the ZG in normal human adrenal glands but that DAB2 immunostaining is not sufficiently powerful for histopathological diagnosis of APA. DAB2 might be involved in excessive aldosterone biosynthesis and correlate with specific clinical characteristics of APA patients.